The Effect Of The Synectics Learning Model On Students’ Ability To Write Short Stories At Grade VII MTs Pondok Pesantren Al-Muktariah Sungai Dua - Robianna Harahap; Rina Devianty (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study was motivated by the low ability of students in writing short stories, which was generally limited to simple ideas, incoherent plots, and a lack of conflict exploration. The learning model applied by teachers was still conventional and less effective in encouraging students’ creativity. The purpose of this study was to investigate the effect of the synectics learning model on students’ ability to write short stories at grade VII MTs Pondok Pesantren Al-Muktariah Sungai Dua. This research employed a quasi-experimental method with a pretest-posttest control group design. The subjects were two classes, with the experimental class taught using the synectics model and the control class taught using a conventional model. The instrument was a short story writing test analyzed through normality, homogeneity, and independent t-test. The results showed that both groups had relatively similar initial abilities, but after treatment there was a significant difference with t = 4.989; p = 0.000. The mean posttest score of the experimental group (76.70) was higher than the control group (67.73). The conclusion is that the synectics learning model has a significant effect on improving students’ short story writing ability. This finding reinforces the theory that analogy and conflict exploration in synectics effectively stimulate creativity, enrich narrative ideas, and enhance students’ motivation to write.